Mathematical algorithm for the automatic recognition of intestinal parasites - Alva, A (2017)
This study was funded by CONCYTEC-PROCYT 245-2008 and FINCyT-EQUIP 100-2009. MZ was a grantee of Bill and Melinda Gates Foundation (OPPOPP1140557). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.